Relationship Between Risk-Adjustment Tools and the Pediatric Logistic Organ Dysfunction Score. (January 2014) - Russell, Rebecca A.; Ghanayem, Nancy S.; Kuhn, Evelyn M.; Jeffries, Howard E.; Scanlon, Matthew C.; Rice, Tom B.
Background: The Risk-Adjusted Classification for Congenital Heart Surgery (RACHS-1) method and Aristotle Basic Complexity (ABC) scores correlate with mortality. However, low mortality rates in congenital heart disease (CHD) make use of mortality as the primary outcome measure insufficient. Demonstrating correlation between risk-adjustment tools and the Pediatric Logistic Organ Dysfunction (PELOD) score might allow for risk-adjusted comparison of an outcome measure other than mortality. Methods: Data were obtained from the Virtual PICU Systems database. Patients with postoperative CHD between 2009 and 2010 were included. Correlation between RACHS-1 category and PELOD score and between ABC level and PELOD score was examined using Spearman rank correlation. Consistency of PELOD scores across institutions for given levels of case complexity was examined using Kruskal-Wallis nonparametric analysis of variance. Results: A total of 1, 981 patient visits among 12 institutions met inclusion criteria. Positive correlations between PELOD score and RACHS-1 category ( r s = .353, P < .0001) as well as between PELOD score and ABC level ( r s = .328, P < .0001) were demonstrated. Variability in PELOD scores across individual centers for given levels of case complexity was observed ( P < .04). Conclusions: Risk-Adjusted Classification for Congenital Heart Surgery categories and ABC levels correlate with postoperative organ dysfunction as measured by PELOD. However, the correlation was weak, potentially due to limitations of the PELOD score itself. Identification of a more accurate metric of morbidity for the congenital heart disease population is needed.